La maldición de la piedra: Víctima expiatoria y crisis social en Los recuerdos del porvenir - Chen Sham, Jorge (2015)
The transformation from human being to stone suffered by Isabel at the end of the novel, must be interpreted in a negative way, since the personal failure brings consequences for the whole collective. We have to remember that getting into stone is a curse sign within the symbolic-mythic thought. Then, Isabel's death-sentence works as the angular stone of the longed purification needed by the Ixtepec society in order to neutralize the divine punishment, and invoke the story continuity of the endemic but collective failure. Isabel is the necessary victim found by Los recuerdos del porvenir, in order to fulfill the social evils and neutralize the current crisis.